Analisis Penerimaan Pengguna E-Wallet DANA Menggunakan Metode TAM dan Delone Mclean - Sari, Gusmelia Puspita; Salisah, Febi Nur; Rozanda, Nesdi Evrilyan; Afdal, M; Jazman, Muhammad; Marsal, Arif (Journal of Information System Research (JOSH), 2024)
The industrial revolution 4.0 motivates advances in information technology through the idea of ​​the internet of things (IoT). One form of implementing the internet of things is the use of e-wallets as a payment medium. One e-wallet that is popular among users is the DANA application. The DANA application helps users make non-cash or cardless payments, making transactions easier and more practical. Despite the advantages offered, there are several problems in its implementation, such as delays when making transfers, not being able to top up and losing balance. Therefore, using the TAM and Delone Mclean approach, this research aims to analyze user acceptance of the DANA application as an effort to see what factors make the DANA application able to be accepted and used by many users. This research was conducted on DANA application users who live in Pekanbaru City with a sample size of 100 respondents. The research uses quantitative methods by distributing questionnaires online. The data that has been collected is processed first using Microsoft Excel, then continued using SmartPLS 4 to analyze PLS-SEM. From hypothesis testing, the results obtained were that seven hypotheses were accepted and declared positive and significant, while one hypothesis was rejected because it did not show a significant relationship.